Sources of viral respiratory infections in Canadian acute care hospital healthcare personnel. Issue 4 (April 2020) - ; Hatchette, T.; Holness, L.; Raboud, J.; Langley, J.; Mazzulli, T.; Nichol, K.; Genesove, L.; Oudyk, J.; McCaskell, L.; Johnson, N.; Buckrell, S.; et al.
Summary: Background: Viral respiratory illnesses are common causes of outbreaks and can be fatal to some patients. Aim: To investigate the association between laboratory-confirmed viral respiratory infections and potential sources of exposure during the previous 7 days. Methods: In this nested case–control analysis, healthcare personnel from nine Canadian hospitals who developed acute respiratory illnesses during the winters of 2010/11–2013/14 submitted swabs that were tested for viral pathogens. Associated illness diaries and the weekly diaries of non-ill participants provided information on contact with people displaying symptoms of acute respiratory illness in the previous week. Conditional logistic regression assessed the association between cases, who were matched by study week and site with controls with no respiratory symptoms. Findings: There were 814 laboratory-confirmed viral respiratory illnesses. The adjusted odds ratio (aOR) of a viral illness was higher for healthcare personnel reporting exposures to ill household members [7.0, 95% confidence interval (CI) 5.4–9.1], co-workers (3.4, 95% CI 2.4–4.7) or other social contacts (5.1, 95% CI 3.6–7.1). Exposures to patients with respiratory illness were not associated with infection (aOR 0.9, 95% CI 0.7–1.2); however, healthcare personnel with direct patient contact did have higher odds (aOR 1.3, 95% CI 1.1–1.6). The aORs for exposure and for direct patient contact were similar for illnesses caused by influenza. Conclusion: Community and co-worker contacts are important sources of viral respiratory illness in healthcare personnel, while exposure to patients with recognized respiratory infections is not associated. The comparatively low risk associated with direct patient contact may reflect transmission related to asymptomatic patients or unrecognized infections.